2017
DOI: 10.2217/bmm-2017-0362
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Anti-GM-CSF Autoantibody Levels in Autoimmune Pulmonary Alveolar Proteinosis

Abstract: Our results indicate the existence of threshold levels of serum anti-GM-CSF IgG for the development and persistence of aPAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Recently, Nakata et al validated a new serum GMAb testing kit and provided an optimal cut-off value for these individuals [29]. Several studies have evaluated GMAb levels in other lung diseases [5,8,20]. Nishimura et al demonstrated the cut-off serum GMAb values measured by ELISA to discriminate aPAP from healthy controls or other lung diseases as 2.0 μg/mL (sensitivity 100%, specificity 100%) or 2.8 μg/mL (sensitivity 100%, specificity 98%) [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Nakata et al validated a new serum GMAb testing kit and provided an optimal cut-off value for these individuals [29]. Several studies have evaluated GMAb levels in other lung diseases [5,8,20]. Nishimura et al demonstrated the cut-off serum GMAb values measured by ELISA to discriminate aPAP from healthy controls or other lung diseases as 2.0 μg/mL (sensitivity 100%, specificity 100%) or 2.8 μg/mL (sensitivity 100%, specificity 98%) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated GMAb levels in other lung diseases [5,8,20]. Nishimura et al demonstrated the cut-off serum GMAb values measured by ELISA to discriminate aPAP from healthy controls or other lung diseases as 2.0 μg/mL (sensitivity 100%, specificity 100%) or 2.8 μg/mL (sensitivity 100%, specificity 98%) [20]. They reported that GMAb levels in sarcoidosis and pneumoconiosis patients were slightly higher than those in healthy controls [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report of dust-related PAP with anti-GM-CSF antibody discussed a case caused by occupational exposure to indium-tin oxide for 4 months (12). Additionally, anti-GM-CSF antibodies were reported to be positive in many patients with pneumoconiosis who merged PAP (13). However, there are no reports on PAP with anti-GM-CSF antibody detected after one-time exposure to dust.…”
Section: Discussionmentioning
confidence: 99%